THE ROLE OF INSTRUCTIONAL DESIGN IN DEVELOPING TACTICAL AND STRATEGIC SKILLS IN WRESTLERS: CRITICAL LITERATURE REVIEW - Robiah; Eliagus Telaumbanua; Munir Tubagus; Mustopa; Abdul Wahab Syakhrani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study explores the transformative role of instructional design in developing tactical and strategic skills among wrestlers. The investigation delves into critical instructional design principles, including establishing clear learning objectives and developing structured learning materials. Additionally, it examines technology integration, such as virtual applications and video analysis, and the motivational factors essential for practical skill development. A comprehensive case study illustrates the practical application of instructional design principles in a wrestling training program. The analysis not only evaluates changes in tactical and strategic skills but also considers the holistic impact on overall athlete outcomes. Findings emphasize the multifaceted benefits of instructional design, influencing physical conditioning, mental resilience, and match performance. Decision-making under pressure and adaptability during live competition are qualitative dimensions shaped by instructional design strategies. As wrestling continues to evolve, this study underscores the indispensable role of instructional design in optimizing the learning experience and maximizing athletes' potential in this demanding sport.